Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Berpikir Kritis Siswa Kelas X Di SMA Negeri 11 Kota Jambi - Aldilah, Tia Rosa; Sari, Pratiwi Indah (Universitas Batanghari Jambi, 2024)
This research aims to determine the effect of using the Problem Based Learning learning model on the critical thinking abilities of class X students at SMA Negeri 11 Jambi City. This type of research uses quantitative research methods with a descriptive analysis approach and simple linear regression analysis techniques. The results of the research show that the use of the Problem Based Learning learning model has a significant and positive effect on the critical thinking abilities of class X students at SMA Negeri 11 Jambi City. Thus, Problem Based Learning carried out in class X at SMA Negeri 11 Jambi City can improve students' critical thinking.